State of pre-competitive anxiety among swimmers and water polo players in relation to competitive experience - Thanopoulos, V. (Biomechanics and Medicine in Swimming X, 2006)
This research aims at examining differences in the intensity of pre-competitive anxiety based on competitive experience between - a) the two sexes (male and female) and - b) the two sports (swimming and water polo). In the research participated 601 male and female athletes, aged 13-26 yrs old of which 425 were swimmers and 176 were water polo players? Their competitive experience varied from 1-13 yrs and according to this they were divided in five /S/ groups. As regards the sample sex it consists of 288 males and 313 females. The athletes completed, before the event the Greek Version of the Competitive State Anxiety Inventory questionnaire (CSAI - 2; Marthens at al., 1990; Kakkos & Zervas; 1996). The results show that in relation to gender, there is a statistically significant difference in three factors of anxiety. With respect to the competitive experience criterion, there is a significant statistical difference only with regard to the factor of self-confidence as well as to the criterion of competitive experience in relation to the sport regarding the all three anxiety factors.